Penerapan Nilai Wajar Dalam Penilaian Aset Perusahaan pada Bank Permata Tbk Tahun 2019-2021 - Alya Ardianti Lahfah; Imas Maskupah; Zahra Nelfa Faradisyi (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
The financial statements present the financial position using the historical cost method, but PSAK 68 as a consequence of the application of IFRS 13 requires that some financial statements are determined using the fair value method. Companies in Indonesia require the application of fair value accounting because the financial sector, especially the banking sub-sector, plays a very important role in driving Indonesia's economic development. The object in this research is Bank Permata Tbk in 2019-2021. This study uses secondary data from the annual report of PT Bank Permata. This research uses a case study on the application of fair value related to the valuation of assets of PT Bank Permata Tbk. The analysis in this study is descriptive analysis, which is used to process quantitative data. The overall result of fair value measurement of asset valuation from the banking industry in PT. Bank Permata Tbk has been considered as appropriate, it is due that 19 out of 20 questions were answered in accordance with the PSAK 68. Based on result of analysis, it is found that the question number 12 were not answered in accordance with PSAK 68 paragraph 74 with regards to the entities is prioritize the fair value hierarchy compare than the input, in other hand according to PSAK 68 paragraph 74 the priority should be the input than fair value hierarchy.